ILMU ḤUḌŪRĪ Khazanah Epistemologi Islam - Saidurrahman Saidurrahman (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2014)
Abstract: Knowledge of the presence (ḥuḍūrī) with mystical experience as describe above is deemed the most popular models of knowledge in Islamic philosophy at the same coloring methodology and epistemology of Islam. Through logical arguments, semantic analysis and epistemo¬logy sharp Suhrawardī considered very successfully demonstrate authenticity huduri science as a science model of non-representational. Among the classical epistemological problems that have not been resolved until now -but able to be dissected in clear and distinct- is about the relationship of subject and object of knowledge, that is the problem more acute in modern Western philosophy. What is interesting is when when to review the issues very carefully and consistently Mehdi directing and bringing the students (who interest in Islamic philosophy) into the recesses of the inner world and the dialogue with the depth of their own existence. It is undeniable that Ha'iri Mehdi Yazdi take existentialist philosophy illumination Suhrawardī and MullaṢadrā as a main reference, as he learned the lesson of Plato, Aristotle, Plotinus, Ibn Sīnā, and al-Ṭūsī, citing the idea of a number of Western philosophers were actually familiar with the science huduri that he wanted to offer. However unique, he expertly directs their ideas to the conclusion that it is inevitable for us to acknowledge the existence of non - phenomenal knowledge. Abstrak:Pengetahuan dengan kehadiran (ḥuḍūrī) dibarengai pengalaman mistik seperti yang paprkan diatas dipandang model pengetahuan yang paling populer dalam filsafat Islam sekaligus mewarnai metodologi dan epistemologi Islam. Melalui argumen-argumen logis, analisis semantik dan epistemologi yang tajam Suhrawardī dipandang sangat berhasil mendemonstrasikan keautentikan ilmu huduri sebagai sebuah model ilmu non-representasional. Diantara problem-problem klasik episte-mologis yang belum terselesaikan hingga kini—tetapi mampu dibedah secara clear dan distink—adalah tentang hubungan subjek dan objek pengetahuan, yang problemnya makin akut dalam filsafat Barat modern. Yang menarik adalah ketika ketika mengulas masalah-masalah itu Mehdi sangat cermat dan konsisten mengarahkan dan membawa para murid-muridnya (peminat filsafat Islam) memasuki relung-relung dunia batin dan berdialog dengan kedalaman eksistensi mereka sendiri. Tak dapat dipungkiri bahwa Mehdi Ha’iri Yazdi mengambil filsafat iluminasi Suhrawardī dan eksistensialis MullaṢadrā sebagai acuan utamanya, seraya memetik pelajaran dari Plato, aristoteles, Plotinus, Ibn Sīnā, dan al-Ṭūsī, mengutip gagasan sejumlah filosof Barat yang sebetulnya asing dengan ilmu ḥuḍūrī yang hendak ia tawarkan. Akan tetapi uniknya, dengan piawai ia mengarahkan gagasan-gagasan mereka kepada penarik¬an kesimpulan bahwa adalah tak terelakkan bagi kita untuk mengakui eksistensi pengetahuan non-fenomenal itu. Keywords: ilmu ḥuḍūrī, khazanah, epistemologi, cogito ergo sum, atheisme.